A New System of Generalized Variational Inclusions Involving $H$-$η$-Monotone Operators in Uniformly Smooth Banach Spaces (Communications in Mathematical Research, 2021)
In this paper, we introduce and study a new system of generalized variational inclusions involving $H$-$η$-monotone operators in uniformly smooth Banachspaces. Using the resolvent operator technique associated with $H$-$η$-monotone operators, we prove the approximation solvability of solutions using an iterative algorithm. The results in this paper extend and improve some known results from the literature.
Keywords: uniformly smooth Banach space; $H$-$η$-monotone operator; resolvent operator technique; system of generalized variational inclusion; iterative algorithm.